2021
DOI: 10.3390/biology10070628
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a Seedling Phenotyping Strategy to Support European Wheat Breeding Focusing on Leaf Rust Resistance

Abstract: Leaf rust resistance is of high importance for a sustainable European wheat production. The expression of known resistance genes starts at different developmental stages of wheat. Breeding for resistance can be supported by a fast, precise, and resource-saving phenotyping. The examination of detached leaf assays of juvenile plants inoculated under controlled conditions and phenotyped by a robotic- and computer-based, high-throughput system is a promising approach in this respect. Within this study, the validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Therefore, selection of stable highly resistant genotypes could be done in this experiment. Similar degree of broad-sense heritability was reported previously for LR seedling resistance ( Gao et al, 2016 ; Beukert et al, 2021 ). Such high degree of broad-sense heritability promised with a genetic improvement for leaf rust resistance against a wide range of Pt populations.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, selection of stable highly resistant genotypes could be done in this experiment. Similar degree of broad-sense heritability was reported previously for LR seedling resistance ( Gao et al, 2016 ; Beukert et al, 2021 ). Such high degree of broad-sense heritability promised with a genetic improvement for leaf rust resistance against a wide range of Pt populations.…”
Section: Discussionsupporting
confidence: 87%
“…However, the degree of broad-sense heritability for PstHI was lower than PstFI which suggested that PstHI is more affected by the environment. High degrees of wheat resistance to PstFI were reported previously [4,9,14,41,42].…”
Section: Phenotypic Evaluation Of Stripe Rust Foliar and Head Infectionmentioning
confidence: 72%
“…However, if resistance quantification performed in controlled conditions is to be of value, there must be a strong correlation between these data and true resistance in the field. In their study, Beukert et al [ 29 ] reported an approach aiming at identifying seedling leaf-rust resistance in European wheat elite lines, combining detached-leaf assay with high throughput screening with a robot (Macrobot platform). Even if correlation remained moderate (0.38–0.45) between in vitro assays and adult plant resistance, the results are promising and there is room to improve this approach, especially with regards to the diversification of rust strains.…”
mentioning
confidence: 99%